Art That Breathes: Lewis deSoto’s Paranirvana (self-portrait) - Montiel, Anya (Conversations, 2014)
Unlike its solid stone predecessor, deSoto’s work, made from painted polyethylene cloth, is hollow, filled only by air from a fan that keeps the sculpture inflated. The resemblance to the reclining Buddha is nonetheless remarkable, from the curls of hair to the folds of the robe, the one exception being that deSoto superimposed his own facial features, complete with goatee, on this Buddha.